In their own eyes: an empirical examination of police self-legitimacy - Tankebe, Justice (International journal of comparative and applied criminal justice, 2019)
In their paper Beyond Procedural Justice, Bottoms and Tankebe specified two interrelated dimensions of legitimacy: audience legitimacy and self-legitimacy. Criminologists have given considerable attention to audience legitimacy, but police officers’ belief in their own legitimacy remains understudied. This paper extends Bottoms and Tankebe’s theory and reports findings on some of its key propositions, using survey data from a UK police force. Three key findings emerge. First, contrary to previous studies, feelings of recognition by supervisors and clientele did not predict self-legitimacy; self-legitimacy was found to depend on feelings of peer recognition and acceptance. Second, self-legitimacy predicted officers’ commitment to external procedural justice but not their moral orientations towards crime victims. Finally, perceived police effectiveness but not supervisor recognition - that is, internal procedural justice - was the key predictor both of external procedural justice and of normative orientations towards crime victims. The implications of these findings are discussed.